2000
DOI: 10.1002/(sici)1099-0844(200006)18:2<143::aid-cbf857>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iodide on total antioxidant status of human serum

Abstract: Free radicals and subsequent lipid peroxidation have been implicated in the pathogenesis of several degenerative and chronic diseases which are also treated frequently in spas. There are some data arising from previous studies which support an antioxidant or scavenging effect of iodide, being the essential ingredient of a therapeutically used local brine. The aim of the study was to test the antioxidant capacity of iodide in human serum. For this reason we measured the so-called Total Antioxidant Status determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Berking et al (37) demonstrated the antioxidant action of Iin polyps of the jellyfish Aurelia aurita, whereas Elstner and co-workers found this antioxidant effect in the rabbit eye (38). Micromolar amounts of Idecrease damage by free oxygen radicals, increase the total antioxidant status in human serum (39,40), and defend brain cells in rats from lipid peroxidation (41). Thyroxine and other iodothyronines act as antioxidants and inhibitors of lipid peroxidation after they are oxidized by hemoglobin and their iodine is released (42,43).…”
Section: Antioxidative Effectsmentioning
confidence: 99%
“…Berking et al (37) demonstrated the antioxidant action of Iin polyps of the jellyfish Aurelia aurita, whereas Elstner and co-workers found this antioxidant effect in the rabbit eye (38). Micromolar amounts of Idecrease damage by free oxygen radicals, increase the total antioxidant status in human serum (39,40), and defend brain cells in rats from lipid peroxidation (41). Thyroxine and other iodothyronines act as antioxidants and inhibitors of lipid peroxidation after they are oxidized by hemoglobin and their iodine is released (42,43).…”
Section: Antioxidative Effectsmentioning
confidence: 99%
“…It could be shown that iodide inhibits the free radical-induced depolymerisation of hyaluronic acid measured by its decrease of in viscosity. This antiradical effect has been shown significantly down to concentrations In vitro studies with human serum showed an increase in the total antioxidant status (TAS) by a colorimetric method at a concentration beginning with 0.7 µM iodide [9], as well as an increase in peroxidase activity [10]. Accordingly, there was a decrease in the peroxide level in this concentration range (Figure 3).…”
Section: In Vitro Findingsmentioning
confidence: 87%
“…The TAS assay has proven to be a relatively simple and useful method for estimating antioxidant capacity in serum 42. The assay is based on the scavenging effect of antioxidants on 2,2′‐azino‐bis(3‐ethylbenzthiazoline‐6‐sulfonic acid) radicals (ABTS + ) 43.…”
Section: Discussionmentioning
confidence: 99%